Argumento, argumentação e auditório universal: a nova retórica de Perelman - Lazarotto, Claudia Candida (2009)
This dissertation presents the bases on which Chaïm Perelman and Lucie Olbrechts-Tyteca settled their Traité de l'argumentation: la nouvelle rhétorique [The new rhetoric: a treatise on argumentation], in the restructuring context of creating concepts and rhetoric of universal audience and the spirit of community , leading to the construction of an idealized community of communication where all subjects are perceived with the same capacity for understanding and communication. Speaker and audience in this community recognize the rationality of their discussions and arguments based on agreements based on the system of beliefs, accepting the arguments of plausible, of likelihood, of probable, assuming the free argumentative rather than coercive argument. In this case, speaker and audience engage in a context of mutual construction training in the auditorium of what is universal and the community of spirits that Perelman s theory act as a legitimate institution of the actions of speech that occur between speaker and audience.